Methyl Ester production using feedstock and catalysts from waste sources - Irma, Nurfitri (2015)
In the present work, waste sources, namely boiler ash, baby clam (Paphia undulata) shell and capiz (Placuna placenta) shell have been successfully utilized as solid catalysts in the transesterification of palm olein (RBD-PO) and waste palm cooking oil (WPCO) to produce methyl esters (biodiesel). In order to enhance the catalytic activity, the boiler ash had been calcined at 500 ˚C for 5 h (was labelled as BA-500), while waste shells of baby clam and capiz have been calcined at 900 ˚C for 2 h (labelled as BCCaO-900 and C-CaO-900, respectively). The optimal reaction conditions found to be: for transesterification of RBD-PO and WPCO using BA-500 as a catalyst were 3 wt.% catalyst amount (based on oil weight) and 9:1 methanol to oil molar ratio for 1 h reaction period, while BC-CaO-900 and C-CaO-900 with 5 wt.% catalyst amount, 12:1 methanol to oil molar ratio for 3 h reaction period. All catalysts achieved over 96.5% methyl ester content at the reflux temperature of methanol (65 ˚C). Furthermore, the mixed-shell catalyst of BC-CaO and C-CaO (labelled as BC-C-Mixed-900) at a 1:1 weight ratio showed similar activity as the individual catalysts. The regenerated of the catalytic activity was investigated, and found that the BA-500 could be reused up to two times, while BC-C-Mixed-900 catalyst reused up to seven times when maintaining methyl esters content above 90%. In addition, the BA and BC-C-Mixed-900 catalysts exhibit tolerance towards the presence of water at 1.75% and 2.0% and free fatty acid at 1.75% and 1.75%, respectively, with over 80% of methyl esters content. Oil extracted from decanter cake (DC) was also investigated in this study, via in situ transesterification with ultrasonic irradiation and mechanical stirring method. The catalyst amount of 20 wt.% (based on oil weight), 150:1 methanol to oil molar ratio, cosolvent: DC (1:1) weight were found as the optimal conditions, yielding 86% and 45% methyl ester content in an hour reaction period for ultrasound irradiation and mechanical stirring, respectively. The emissions performance of WPCO B10 blend using BA-500 as a catalyst was investigated on horizontal single cylinder 4-stroke diesel engine (YANMAR NF19-SK). The results indicated that the WPCO B10 blend biodiesel gives lower CO2 and CO emission compared to commercial diesel, thus contributed to the reduction of greenhouse gases